Inequality, cumulative disadvantage and youth justice: Towards an analytical framework for understanding and addressing inequalities in youth justice decision-making - Brink, Yannick Nelson van den (International journal of law, crime and justice, 2025)
Demographic inequalities in law enforcement practices and subsequent youth justice decisions are well-documented in many youth justice systems worldwide. Informed by the concept of ‘cumulative disadvantage’ and empirical evidence from England & Wales and the Netherlands, this paper explores how inequalities in youth justice decisions are produced, how they might move and accumulate across different stages of the youth justice process and interact with inequalities in interlocking systems, specifically the educational system and the child protection system. Subsequently, this paper presents the first contours of an overarching analytical framework which can be used to unpack the complex web of dynamics, interactions and mechanisms that produce and reinforce inequalities in youth justice decisions. The analytical framework distinguishes seven spheres of influence - from the micro to the macro - that shape youth justice decision-making, out of which inequalities might develop and accumulate. These spheres of influence illustrate that interactions between individuals, agencies and systems as well as the wider societal context are all implicated in the mechanisms of creating, sustaining or amplifying children's inequalities and disadvantages in youth justice. Overall, by illuminating the complexity and the multidimensional nature of mechanisms of inequality and cumulative disadvantage in youth justice decision-making, the presented analytical framework offers researchers, policymakers and practitioners much-needed guidance to identify avenues for further inquiry and potential areas for reform, with the aim of effectively addressing unwarranted inequalities in youth justice in England & Wales, the Netherlands and internationally.